Facile Synthesis of Hematite Quantum‐Dot/Functionalized Graphene‐Sheet Composites as Advanced Anode Materials for Asymmetric Supercapacitors. (12th December 2014) - Xia, Hui; Hong, Caiyun; Li, Bo; Zhao, Bin; Lin, Zixia; Zheng, Mingbo; Savilov, Serguei V.; Aldoshin, Serguei M.
<x xml:space="preserve">Abstract</x> For building high‐energy density asymmetric supercapacitors, developing anode materials with large specific capacitance remains a great challenge. Although Fe2O3 has been considered as a promising anode material for asymmetric supercapacitors, the specific capacitance of the Fe2O3‐based anodes is still low and cannot match that of cathodes in the full cells. In this work, a composite material with well dispersed Fe2O3 quantum dots (QDs, ≈2 nm) decorated on functionalized graphene‐sheets (FGS) is prepared by a facile and scalable method. The Fe2O3 QDs/FGS composites exhibit a large specific capacitance up to 347 F g−1 in 1 m Na2SO4 between –1 and 0 V versus Ag/AgCl. An asymmetric supercapacitor operating at 2 V is fabricated using Fe2O3/FGS as anode and MnO2/FGS as cathode in 1 m Na2SO4 aqueous electrolyte. The Fe2O3/FGS//MnO2/FGS asymmetric supercapacitor shows a high energy density of 50.7 Wh kg−1 at a power density of 100 W kg−1 as well as excellent cycling stability and power capability. The facile synthesis method and superior supercapacitive performance of the Fe2O3 QDs/FGS composites make them promising as anode materials for high‐performance asymmetric supercapacitors.